2010
DOI: 10.1590/s1984-82502010000200010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of foam properties of saponin from Ilex paraguariensis A. St. Hil. (Aquifoliaceae) fruits

Abstract: Saponins are natural compounds able to form abundant foam, a desirable quality required in some chemical, foods, cosmetic and pharmaceutical processes. Ilex paraguariensis A. St. Hil. (Aquifoliaceae) known as mate, is a South American widely cultivated specie due to the preparation of a tea-like beverage from its leaves. Moreover, its green fruits are a rich source of non-toxic and very low haemolytic saponins. In this study, mate saponin fraction (MSF) was evaluated as a foam former, focusing on its foamabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
0
16
0
1
Order By: Relevance
“…4 In a study on the effects of tea saponins and different synthetic surfactant mixtures on foam properties, a synergistic effect was reported between saponins and cetyltrimethylammonium bromide or sodium dodecyl sulfate. 5 Canto et al 6 examined the effects of five different electrolytes on foams produced using mate saponin and reported that the foaming power of the saponins did not change according to the electrolytes except for magnesium chloride. However, in all electrolyte solutions, there was a significant decrease in foam height after 1 h. 6 Böttcher and Drusch 1 compared the foaming properties of six different saponin extracts from various plants, with the results showing that tea seed, horse chestnut, quillaja, and soapwort formed stable foams.…”
Section: Introductionmentioning
confidence: 99%
“…4 In a study on the effects of tea saponins and different synthetic surfactant mixtures on foam properties, a synergistic effect was reported between saponins and cetyltrimethylammonium bromide or sodium dodecyl sulfate. 5 Canto et al 6 examined the effects of five different electrolytes on foams produced using mate saponin and reported that the foaming power of the saponins did not change according to the electrolytes except for magnesium chloride. However, in all electrolyte solutions, there was a significant decrease in foam height after 1 h. 6 Böttcher and Drusch 1 compared the foaming properties of six different saponin extracts from various plants, with the results showing that tea seed, horse chestnut, quillaja, and soapwort formed stable foams.…”
Section: Introductionmentioning
confidence: 99%
“…[6,7] The high activity of Quillaja saponin could be attributed to the fact that the extract used by Mitra and Dugan (1997) was that of a commercially available purified powder, while the extracts of Guaiacum used in the present study as well as the extracts of the other mentioned plants are enriched extracts prepared by phase fractioning. The high saponin content in the commercial sample is likely to produce better results because of higher concentrations of saponin in the extract.…”
Section: Resultsmentioning
confidence: 90%
“…The reductions in surface tension of water due to Guaiacum officinale leaf and stem saponin [6] Similarly, a crude extract of Sapindus mukorossi reduced the surface tension of water to 51.7 mN m −1 . [7] Glycyrrhiza glabra saponin extract reduced the surface tension of water to approximately 46 mN m −1 .…”
Section: Resultsmentioning
confidence: 99%
“…2 B, highest foamability observed in the solutions which those were extracted using highest amount of plant root powder and pH value, or minimum amount of the plant root and pH value. Obtained results can be related to the point that, by raising the amount of A. glandulosum root, saponin content also increased which that causing higher foamability [ 22 ]. On the other hand, at strong basic and acidic solutions, surrounded layer made of pectic, cellulosic and hemi cellulosic compounds, which those cover the saponin, were hydrolyzed and maximum amounts of the saponin could be extracted.…”
Section: Resultsmentioning
confidence: 99%